Quantitative Approach for Determining Reproductive Life‐History Strategies of Parasitic Plants: A Case Study in Balanophora - Trevor Padgett; Huei‐Jiun Su; Shu‐Hui Wu; Li‐yen Huang; Yiching Lin (Ecology and Evolution)
ABSTRACT Parasitic plants are a diverse and unique polyphyletic assemblage of flowering plants that survive by obtaining resources via direct vascular connections to a host plant. Ecologically important in their native ecosystems, these typically cryptic plants remain understudied and fundamental knowledge of the biology, ecology, and evolution of most species is lacking. This gap limits our understanding of ecosystems and conservation management. We established a multistep protocol to conduct the first investigation of the reproductive life history of root parasite genus Balanophora, testing the hypotheses of perenniality, cryptic perenniality, and plasticity across five geographically isolated populations in Taiwan. A review of 123 Balanophora publications found contradictory determinations, including no determination (87%), perennial (9%), annual (1%), biennial (1%), or a combination (2%). No primary study investigated the question, and no determination was accompanied by reference. Between 2021 and 2024, we tested a hypothesis of perenniality (109 individuals, 135 patches) and cryptic perenniality (73 host samples), monitored population dynamics (whole population), and potential for endophytic/dormant haustorial tissue (101 roots) across five isolated populations of Balanophora fungosa ssp. fungosa in Taiwan. Our results support semelparous annuality. After reproduction, individuals senesce and die, and the following year's population is recruited from newly germinated individuals which together develop in size and number during a vegetative growth period, undergo reproduction, and then themselves senesce and die. Each cycle is completed within a 12‐month period. Synthesis: Our study provides the first quantitative determination of a semelparous annual reproductive life‐history strategy for any species of Balanophora. This determination is important in our progress toward better understanding the species—and parasitic plants in general—as well as ecological roles within ecosystems and conservation management. Our study further provides a template for future work to expand life‐history strategy determination across cryptic root parasitic plants.